Faktor-Faktor Pengembangan Sistem Informasi Akademik Berbasis Web Pada Perguruan Tinggi Swasta Palembang - Muhammad Soekarno Putra (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
One of the utilization of information technology development in the world of education in private universities (PTS) is by utilizing and implementing web-based academic information system (SIA). This study aims to examine the contribution of technology and infrastructure (IT), design (DS), human resources (SD) and culture (BD) in web-based SIA development at PTS in Palembang. The research method used was quantitative method, while the technique of data collection using questionnaire method. Data analysis method in this study used Structural Equation Modeling (SEM). Population in this research were PTS in Palembang which have web based SIA, they were Universitas Bina Darma and STMIK Palcomtech. While the respondents were students, lecturers and staff. The results of the research showed that technology and infrastructure, design, human resources and culture contribute to the development of web-based SIA at PTS in Palembang.